Meanings of communication technology in virtual team meetings: Framing technology-related interaction. Issue 111 (March 2018) - Laitinen, Kaisa; Valo, Maarit
Highlights: Virtual team meetings include a significant amount of interaction related to communication technology. Technology-related interaction can be defined by four frame categories: practical, work, user, and relational frame. Virtual team members give versatile meanings to the video conferencing platforms they utilize. Meanings of communication technology are related to its use, users and their interpersonal relationships. Abstract: Communication technology is an essential part of virtual teams in working life. This article presents a qualitative study on the meanings of communication technology in virtual team meetings. The study was conducted by examining frames of technology-related virtual team interaction. Observational data was gathered from six expert team meetings. Technology-related communication episodes (N = 88) were identified from team interaction and then analyzed by means of frame analysis. Four frame categories were found: the practical frame, work frame, user frame, and relational frame. Team members talked about technological properties and functions as well as giving and receiving technological guidance. They also discussed technology in relation to work tasks, contemplated technology users' attributes, and built and maintained relationships with technology. The results indicate that virtual team members give meanings to communication technology while interacting. Communication technology has several meanings—it is seen as a tool for work, a reason for uncertainty, a useful benefit, a challenge, an object of competence, an entity of technical properties, a subject of guidance, a way to express closeness, and a shared space. The results presented in this article deepen our understanding of the role communication technology plays in the day-to-day interaction of virtual teams. The results recommend developing both technological systems and team members' ways of using them, as well as providing opportunities to negotiate the meanings of technology and thus avoid frame disputes. In addition, ensuring that virtual teams use technological systems that support their unique communicational needs is suggested.